GEGENI TRADITION IN THE CULTURE OF THE TENGGER TRIBE - Dwi Putri Megawati; Amelia Fitri Mustikawati; Adinda Amirah Harliansyah; Hilda Izza Oktaviani (JURNAL LITERASI, 2022)
This research aims to describe the Gegeni tradition found in the Tengger tribe community, East Java. This research is important to carry out because research on the Gegeni tradition found in the Tengger tribe community has never been carried out. This research utilizes descriptive qualitative methods as the basis for the research methodology. The data in this research was obtained through interview techniques, observation and literature study. Based on research, it was found that Gegeni is not only a tradition that has long existed in the Tengger tribe community, but is also a marker of the community's friendly character.